Osteoprotegerin as a Marker of Atherosclerosis in Diabetic Patients. (17th January 2013) - Augoulea, Areti; Vrachnis, Nikolaos; Lambrinoudaki, Irene; Dafopoulos, Konstantinos; Iliodromiti, Zoe; Daniilidis, Angelos; Varras, Michail; Alexandrou, Andreas; Deligeoroglou, Efthymios; Creatsas, George
Abstract : Atherosclerosis is the principal cause of cardiovascular disease (CVD) and has many risk factors, among which is diabetes. Osteoprotegerin (OPG) is a soluble glycoprotein, involved in bone metabolism. OPG is also found in other tissues, and studies have shown that it is expressed in vascular smooth muscle cells. OPG has been implicated in various inflammations and also has been linked to diabetes mellitus. Increased serum OPG levels were found in patients with diabetes and poor glycemic control. Furthermore, prepubertal children with type 1 diabetes have significantly increased OPG levels. Receptor activator of nuclear factor kappa-B ligand (RANKL) is not found in the vasculature in normal conditions, but may appear in calcifying areas. OPG and RANKL are important regulators of mineral metabolism in both bone and vascular tissues. Few data are available on the relationship between plasma OPG/RANKL levels and endothelial dysfunction as assessed using noninvasive methods like ultrasound indexes, neither in the general population nor, more specifically, in diabetic patients. The aim of our review study was to investigate, based on the existing data, these interrelationships in order to identify a means of predicting, via noninvasive methods, later development of endothelial dysfunction and vascular complications in diabetic patients.